Mongolia Quarterly Economic Update, July 2010 - World Bank (Washington, DC, 2017)
The improvement in public finances since last year, coupled with buoyant revenue due to the commodity price recovery, has led to growing pressures for increased government spending. Recently approved budget amendments envisage a 4.5 percent of gross domestic product (GDP) increase in spending on the originally approved 2010 budget, while the Mid-Term Budget Framework (MTBF) for 2011-2013 projects another 12.1 percent of GDP increase in spending in 2011. The main driver for the increases is the execution of promises made by both coalition parties to distribute monthly percentage rate, or MNT 1.5million (around US$1000) to each citizen in the form of cash and non-cash handouts and large public sector wage increases planned for October of this year. If these public spending plans materialize, they will set the stage for a renewed bout of high inflation and a possible return to the macroeconomic vulnerability characteristic of the boom-and-bust cycle of the recent past. In the real sector, the impact of increasing inflation is evidenced through a decline in real wages. The latest informal wage survey indicates that on average, workers' nominal wages have increased by about 10 percent from January 2010 to June 2010; this is because of an increase in job opportunities in the construction sector. Real wages, however, have declined on average due to the significant increase in the consumer price index.